1998
DOI: 10.1074/jbc.273.27.17278
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Binding to Mitochondria Is Regulated by GTP and the Transit Peptide

Abstract: The association between ribosomes and the pore proteins at the endoplasmic reticulum membrane is important to co-translational translocation. To determine if a similar association occurs between the ribosome and mitochondrial membrane protein(s) during protein import in higher eukaryotes, we examined ribosome-mitochondria binding. By using spectral measurements, analysis of mitochondrial associated RNA, and electron microscopy, we demonstrated that ribosomes stably bind to purified rat liver mitochondria in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 42 publications
(35 reference statements)
3
38
0
Order By: Relevance
“…As expected, EDTA treatment of mitochondrion-bound polysome fractions (15,46) led to the complete release of mitochondrion-bound mRNAs, such as ATM1 or COX10 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 77%
“…As expected, EDTA treatment of mitochondrion-bound polysome fractions (15,46) led to the complete release of mitochondrion-bound mRNAs, such as ATM1 or COX10 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 77%
“…Ribosomes associated with the endoplasmic reticulum are involved in the synthesis of proteins for several membrane systems in the cell, in the synthesis of exported proteins, and in the synthesis of proteins localized in certain subcellular organelles such as lysosomes (32). Cytoplasmic ribosomes are also found associated with the outer membrane of mitochondria (33).…”
Section: Discussionmentioning
confidence: 99%
“…48 Ribosome binding in vitro was found to be inhibited in the presence of GTP; however, this inhibition was rescued when ribosomes were charged with a mitochondrial nascent chain, while a nonmitochondrial nascent protein (luciferase) could not induce a similar effect. 49 Thus, it is apparent that the mitochondrial targeting sequence is also important for ribosome binding. In addition, Kellems and colleagues showed that a high-salt treatment of isolated yeast mitochondria resulted in the release of approximately one-third of the bound ribosomes.…”
Section: Experimental Evidence For Localized Translation Near the Mitmentioning
confidence: 99%